Self-assessment accuracy in higher education: The influence of gender and performance of university students. (July 2019) - González-Betancor, Sara M; Bolívar-Cruz, Alicia; Verano-Tacoronte, Domingo
Self-assessment activities are increasingly popular in the classrooms. But regarding self-assessment accuracy, mixed results are reported without clear reasons for this. This article addresses the impact of gender and performance on self-assessment accuracy. To evaluate self-assessment accuracy, peer and professor assessments are used as reference. A research project, relating to the assessment of oral presentations using scoring rubrics, is conducted in two university degrees. Data from 155 self-assessments and more than 12, 000 peer and professor assessments are gathered. The analysis differentiates by degree, gender and level of performance in the assessed competency. The results show that self-assessment accuracy is low and related to the student's gender, that men rate themselves higher than women do, and that even using a scoring rubric, students receiving higher marks from professors are more accurate than students receiving lower marks.